KAJIAN MORFOMETRIK DAN MERISTIK IKAN KEMBUNG (RASTRELLIGER SP) DI PASIA NAN TIGO DAN KOTO XI TARUSAN, SUMATERA BARAT - Putri, Miranda Ika; Suparno, Suparno; Junaidi, Junaidi (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2025)
AbstractContinuous intensive Rastrelliger sp fishing will threaten the availability or sustainability of mackerel resources. This results in a decrease in the Rastrelliger sp population which has an impact on fishermen's income. For this reason, morphological studies are needed that can be used in studies of fish biology, fish physiology, ecology and data collection on the existence or stock of fish. Therefore, the shape of the fish's body is closely related to its habitat and lifestyle. This study aimed to analyze the Morphometrics and Meristic of Rastrelliger sp in Pasia Nan Tigo and Koto XI Tarusan, West Sumatra. This study was conducted in August - October 2024, the location where the Rastrelliger sp samples were taken was TPI Pasia Nan Tigo and Koto XI Tarusan, West Sumatra. The method used in this study is the direct observation method. Furthermore, measurements of morphometric and meristic characters were carried out on Rastrelliger sp that had been obtained according to gender. The data in this study was analyzed descriptively from the results of morphometric and meristic measurements of Rastrelliger sp and then presented in table. Based on the results of the study of Morphometric and Meristic Characteristics of Rastrelliger sp landed in the two locations Pasia Nan Tigo and Koto XI Tarusan, West Sumatra, there are no significant differences in the morphometric and meristic characteristics of fish in the two locations. The type of fish with the morphometric and meristic characteristics is the Rastrelliger kanagurta.